Psychometric Properties of the Grit-S in Chinese Nurses - He, Changjiu; Wu, Dongmei; Yang, Lu; Yang, Lei; Yue, Yuchuan (Frontiers in Psychology, 2021)
Grit, as a positive psychological trait, could affect the stability of nursing workforce and nurses' physical and mental health continuously. The Short Grit Scale (Grit-S) with fewer items than the original Grit Scale was widely used to measure individual trait-level grit. However, the psychological properties of Grit-S among Chinese nurses have not been verified. A self-designed sociodemographic questionnaire was used to investigate 709 Chinese nurses in the study and Short Grit Scale, Big Five Inventory-44, Brief Self-Control Scale, 10-item Connor-Davidson resilience scale and Task Performance Scale were adopted to collect information of grit, personality, self-control, resilience and work performance. The confirmatory factor analysis, Pearson correlation analysis, hierarchical regression analysis and multi-group confirmatory factor analysis were conducted to verify the psychometric properties of the Grit-S. The results demonstrated that the Grit-S had sound validity and reliability among Chinese nurse samples and had good measurement invariance across nurses in general hospitals and psychiatric hospitals. The results of this study provide confidence in using the grit measurement among Chinese nurse in the future.